Penjadwalan Preventive Maintenance Moulding Untuk Efektivitas Produksi Dengan Metode Overall Equipment Effectiveness (Studi Kasus PT. ABC) - M. Abdul Latief (Jurnal Ilmiah Sultan Agung, 2022)
PT. ABC is one of the manufacturers of washing machines and refrigerators in the Semarang Demakarea. During the washing machine production process, breakdowns often occur in the molding of theBottom Cabinet. To calculate the effectiveness value of the Bottom Cabinet using the Overall EquipmentEffectiveness (ORE) Total Productive Maintenance (TPM) method to increase productivity andmaintenance on the Bottom Cabinet molding to prevent 6 big losses (Six Big Losses) Six Big Lossescausing losses include: ( Breakdown Losses, Set-up and Adjustment Losses, Idling I and MinorStoppages Losses, Reduce Speed Losses, Process Defect Losses, Reduce Yield Losses). Based on thecalculation results of the OEE value in the Molding Bottom Cabinet during December 2021 - June 2022,the Availability Rate value of 93.08% met the JIPM standard value of 90%, Performance Rate = 94.37%did not exceed the 95% JIPM standard, Quality Rate 95 30 % does not meet the 99% JIPM standard,and the resulting OEE-83.72% production is not considered world class. The value of Six Big Losseswhich has the largest percentage is Breakdown Losses 41.31%, Speed Losses 26.93%, Reduce DefectLosses 15.79%, Reduce Yield Losses 9.07%, Set-up and Adjustment Losses 4.97%, Idling and MinorStoppages Losse: 1.93% And to reduce the value of breakdown losses, preventive scheduling is neededin the Molding Bottom Cabinet to increase its effectiveness.Key Word :Total Productive Maintenance (TPM), Overall Equipment Effectivennes(OEE), Six BigLosses, Scheduling Preventive Maintenance